IMPLEMENTASI PELATIHAN BERBASIS DIGITAL MARKETING DALAM MENINGKATKAN MOTIVASI BERWIRAUSAHA BAGI PELAKU UMKM KOTA CIMAHI - Ade Sadikin Akhyadi; Oong Komar; Cucu Sukmana (Abdimas Siliwangi, 2021)
During the pandemic period, economic activities must adjust to limited interactions, minimizing physical contact during the buying and selling process. Of course, the ongoing pandemic period adds to the difficulty of MSME actors, not only to develop, even including maintaining a business. In order to help survive the pandemic, MSME players in Cimahi are deemed necessary to get digital marketing-based training for Cimahi City MSMEs. This service aims to describe the implementation of a digital marketing training program in increasing entrepreneurial motivation for Cimahi City MSMEs. This research is a case study research on MSMEs who take digital-based training. To reveal the data and information, the researchers applied a descriptive study with a qualitative approach, namely revealing the depth of data and information based on research formulations and research questions, namely how to implement a digital marketing training program in increasing entrepreneurial motivation for Cimahi City MSMEs? The digital marketing training system in its cycle is divided into three stages, namely, the planning, implementation, and evaluation stages. Of the three cycles, the implementation of digital marketing-based training begins with a needs analysis, then a digital marketing training design is prepared which is followed by the development of digital marketing training materials, the implementation of training and ends with an evaluation